Magnesium-modified biochar was used to adsorb phosphorus from wastewater and used as a phosphorus source to be recycled to reduce the ammonia nitrogen of piggery digestive wastewater. (1st August 2022) - He, Lintong; Wang, Dehan; Wu, Zhaoyun; Lv, Yongzhen; Li, Sicheng
Abstract: High concentrations of ammonia nitrogen in piggery digestive wastewater are toxic to the microorganisms in wastewater treatment systems. The ammonia nitrogen load can be decreased by struvite precipitation. The purpose of this paper was to take phosphate from magnesium-modified biochar adsorbed wastewater as a phosphorus source and add it to biogas slurry to reduce the ammonia nitrogen concentration. The effects of phosphorus source dosage, initial reaction pH value and reaction time on ammonia nitrogen removal from biogas slurry were investigated, and then the subsequent biogas slurry underwent sequencing batch reactor biochemical treatment. When the phosphorus source dosage was 20 g/L, initial reaction pH value was 10.0 and reaction time was 1 h, the NH3 –N recovery was 62.98%. The subsequent biogas slurry met the discharge standards (DB44/613–2009) after biochemical treatment. An innovative process for the recycling of pig farm waste, nitrogen and phosphorus recovery and advanced treatment of biogas slurry is first proposed in this paper. Graphical abstract: Image 1 Highlights: Mg@C was prepared by pyrolysis of pig manure and waste residue containing magnesium. Mg@C adsorbed PO4 3− from SBR effluent as a phosphorus source for MAP reaction. After MAP reaction, the NH3 –N concentration in biogas slurry was below 200 mg/L. After MAP reaction, SBR effluent more easily met the discharge standard than CK.